Transnational mobility of Chinese students among Portuguese-speaking countries: The role of a non-hegemonic language - Gaspar, S.; Mathias, D. (Journal of Chinese Overseas, 2023)
The idea that the acquisition of and proficiency in non-hegemonic languages can be pivotal to international student mobility has thus far been insufficiently addressed. In this paper, we draw on 23 in-depth interviews with Chinese students to explore this question, showing how the perception of Portuguese-language learning and practice at Lusophone Higher Education Institutions (e.g., in Portugal, Macao, Angola, and Brazil) represents a decisive trigger for studying abroad, and an alternative strategy for acquiring linguistic capital in a non-dominant language in which skills can be converted into competitive resources on future professional paths. We conclude by arguing for the need to address this blind spot in transnational student mobilities, and by positioning “language acquisition and proficiency” as a structuring dimension, not just of the processes by which students decide to move, but also of their imaginaries of preparedness for their future career trajectories.